“When the class goes on too long, the Devil takes part in it”: adab al-muḥaddith according to Ibn aṣ-Ṣalâḥ ash-Shahrazûrî (d. 643/1245) - Jens Scheiner (Revue des Mondes Musulmans et de la Méditerranée)
The two chapters in Ibn aṣ-Ṣalâḥʼs (d. 643/1245) Muqaddima on the proper behaviour of teachers and students of ḥadîth (adab al-muḥaddith) form the core of this study. Therein Ibn aṣ-Ṣalâḥ advices the muḥaddithûn how to conduct a class of ḥadîth. For the students he offers moral guidelines, recommends a particular curriculum and gives practical pedagogical advice. The search for possible precursors led to the main argument of this study, i.e. that Ibn aṣ-Ṣalâḥ used ʿAbd al-Karîm as-Samʿânîʼs (d. 562/1166) work Adab al-imlâʾ wa-ʼl-istimlâʾ as a direct source. Although Ibn aṣ-Ṣalâḥ modeled his Muqaddima after al-Ḥâkim an-Naysâbûrîʼs (d. 405/1014) Kitâb maʿrifat ʿulûm al-ḥadîth there are – quite unexpectedly – only minor similarities in both works regarding issues of adab al-muḥaddith. Taking the adab al-muftî or adab al-qâḍî literature as a model, the article finally argues that simultaneously with the canonization of ḥadîth, Muslim scholars, in particular al-Ḥâkim an-Naysâbûrî, proposed rules according to which ḥadîth had to be taught.